Serum drug levels and anti-drug antibodies in the context of dose tapering by interval prolongation of adalimumab, etanercept and ustekinumab in psoriasis patients: results of the CONDOR trial - Selma Atalay; Sophie E. Berends; Hans M. M. Groenewoud; Ron A. A. Mathot; David M. Njoo; Johannes M. Mommers; Paul M. Ossenkoppele; Marjolein I. A. Koetsier; Maartje A. Berends; Annick de Vries; Peter C. M. van de Kerkhof; Alfons A. den Broeder; et al. (Journal of Dermatological Treatment)
Background Biologics for psoriasis are registered in standard dosages. In patients with low disease activity, reduction of the dose by interval prolongation can prevent overtreatment, and lower risks and costs. However, fear for increased anti-drug antibody (ADA) formation due to interval prolongation of biologics is an important barrier.Objective To investigate the course of serum drug concentrations, ADA levels, and predictors for successful dose reduction of adalimumab, ustekinumab, and etanercept for psoriasis.Methods Patients were randomized to dose reduction (DR) or usual care (UC) and followed for one year. The course and extent of detectable ADA levels were expressed as proportions/relative risks for DR vs. UC. Association of baseline characteristics with successful tapering was investigated with log-binomial regression analysis.Results In total, 118 patients were included. In adalimumab-treated patients, no significant difference in the proportion of patients with relevant ADA levels in DR vs. UC was seen. For ustekinumab, relevant ADA development was absent in both groups. Baseline trough levels were not predictive for successful DR.Conclusions Immunogenicity may not increase by interval prolongation in psoriasis patients with low disease activity. This pilot provides important and reassuring insight into the pharmacological changes after dose tapering of adalimumab, etanercept, and ustekinumab.